Insufficient Understanding of User Benefits Impedes Open Data Initiatives at Museums / Booth, P., Navarrete, T., & Ogundipe, A. (2022). Museum open data ecosystems: A comparative study. Journal of Documentation 78(4), 761-779. https://doi.org/10.1108/JD-05-2021-0102 - Patterson, Jordan (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2023)
Objective – Using Nardi and O’Day’s (1999) definition of ecosystem as “a system of people, practices, values, and technologies in a particular local environment,” to understand how art museums form their policy to interact with and respond to the various open data (OD) ecosystems in which they operate.Design – Multiple case study consisting of interviews and subsequent qualitative analysis, as well as document analysis.Setting – European art museum OD ecosystems.Subjects – Subjects included 7 management staff members at 3 separate mid-size, art-based museums located in Norway, the Netherlands, and Spain; an unspecified number of representatives from a cultural-policy agency in each of those countries; an unspecified number of government, museum, and research documents from within each museum’s OD ecosystem.Methods – The researchers identified 3 museums with OD initiatives and conducted in-depth interviews with relevant staff members at each institution. The researchers also interviewed representatives from relevant national OD policy-related agencies. The researchers coded their data and developed a list of five key OD “ecosystem components,” which they used to analyze the 3 specific museum ecosystems under consideration.Main Results – Open data initiatives at cultural heritage institutions are subject to a number of internal and external pressures. Museums are typically responsive to their environments, and top-down policy requirements appear to be an effective means of advancing open data initiatives. Nevertheless, the value proposition of open data appears to be insufficiently understood by museum staff and other stakeholders. As a result, museums participate in OD initiatives even when the benefit remains undemonstrated and the use of OD—how and by whom—remains unclear.Conclusion – The needs and wants of OD end-users remain ill-defined and poorly understood. As a result, museums expend resources and effort to supply OD, while remaining uncertain about the return on their investment. Attention to users could result in “more robust information flows between ecosystem components.”